Sosialisasi Ekonomi Kreatif Berbasis Budaya Lokal Bagi Karang Taruna Karangtempel - Wenny Ana Adnanti; Tantri Widiastuti (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The growth of creative economy based on local culture has become a significant driver for advancing local communities. Karang Taruna Karangtempel, as part of the local community, has great potential to develop their creative economy by leveraging the richness of their local culture. However, constraints in entrepreneurship knowledge, market access, and youth involvement hinder the optimization of this potential. The objective of this socialization activity is to empower Karang Taruna Karangtempel to become a catalyst in the development of a sustainable local economy. Through youth empowerment and cultural preservation, it is expected that the local community can experience tangible benefits from the creative economy integrated with local values. The implementation method of this community service activity involves three main stages: (1) Planning and preparation; (2) Socialization and counseling; (3) Evaluation and feedback. Local culture-based creative economic outreach activities for Karang Tempel Youth Organization, it is hoped that it can improve entrepreneurial skills and active participation of the younger generation for community empowerment. Introducing a creative economy based on local culture invites the younger generation to pay attention to the abundant resources in the surrounding environment to choose and make into products that can be used as effective alternative products that have high added value.